Integrasi 8 Golden Rules dalam Desain Antarmuka Sistem Informasi Penggajian - Rahayu, Hartika; Putri, Nisrina Akbar Rizky (Universitas Muhammadiyah Klaten, 2025)
The development of a system is done to help facilitate human work due to its effectiveness and efficiency. The XZY campus study program has used an integrated system in processing data. In terms of summarizing attendance and payroll data, it is still done manually, so a system is needed that can help users summarize this data. The interface design construction is made before system development. There are three previous steps in designing the system display: data collection (needs analysis), website design, and testing. The 8 golden rules are used as guidelines in designing a web display that is easy for users to learn.